Article – On Feminist Legal Methodologies: Spilt, Plural and Speaking Subjects - Heathcote, Gina (feminists@law, 2018)
This article uses Nicola Lacey’s 1998 book Unspeakable Subjects as a prompt to consider the potential of feminist jurisprudence to develop methodologies that focus on the foundational dimensions of law. I therefore explore possibilities for a feminist account of legal subjectivity that uses Lacey’s account of critique, utopias and reform to articulate three interlocking feminist methodologies which I label split subjectivities, plural subjectivities and political responsible listening. I argue that these feminist inspired methodologies draw in understandings of difference and of the centrality of inter-subject relations as the important dimensions of humanness that accounts of autonomy overlook, before challenging the text to further consider which voices, and knowledge practices, remain silenced by feminist legal methodologies. To realise these ideas in strategies for law reform I argue for feminist listening that exercises care through the centring of accounts that emerge from those whose normative universe is more often particularised or discounted in law arrangements. As such, the article addresses legal subjectivity through the lens of intersectionality but with a jurisprudence that seeks to transcends the constraints of identity politics and through attention to indigenous Australian feminisms.